HUBUNGAN ANTARA KETERAMPILAN BERPIKIR KRITIS DENGAN LITERASI SAINS SISWA DALAM PEMBELAJARAN IPA KELAS IV SEKOLAH DASAR DI KECAMATAN DUREN SAWIT, JAKARTA TIMUR - Sri Wahyuningsih; Tunjungsari Sekaringtyas; Julius Sagita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This correlational study aims to investigate the relationship between critical thinking skills and students’ science literacy in Grade IV science learning at elementary schools in Duren Sawit District. The sample of this study consisted of 92 fourth grade students from SDN Duren Sawit 10, SDN Duren Sawit 05, and SDN Duren Sawit 18, located in East Jakarta. The sample was selected using a cluster random sampling technique. The research employed a quantitative method with a correlational approach. Data were collected using essay-based tests and analyzed using a t-test. The analysis results show a positive relationship between critical thinking skills and science literacy, as evidenced by the value of t_count > t_table (7.779 > 1.987). These findings indicate that critical thinking skill can be considered as one of the efforts to improve the science literacy of fourth grade elementary school students.